Characterization of an H2-utilizing enrichment culture that reductively dechlorinates tetrachloroethene to vinyl chloride and ethene in the absence of methanogenesis and acetogenesis. - Maymó-Gatell, X (1995)
We have been studying an anaerobic enrichment culture which, by using methanol as an electron donor, dechlorinates tetrachloroethene (PCE) to vinyl chloride and ethene. Our previous results indicated that H2 was the direct electron donor for rductive dechlorination of PCE by the methanol-PCE culture. Most-probable-number counts performed on this culture indicated low numbers (< or equal to 10(4)/ml)) of methanogens and PCE dechlorinators using methanol and high numbers (> or equal to 10(6)/ml)) of sulfidogens, methanol-utilizing acetogens, fermentative heterotrophs, and PCE dechlorinators using H2. An anaerobic H2-PCE enrichment culture was derived from a 10(-6) dilution of the methanol-PCE culture. This H2-PCE culture used PCE at increasing rates over time when transferred to fresh medium and could be transferred indefinitely with H2 as the electron donor for the PCE dechlorination, indicating that H2-PCE can serve as an electron donor-acceptor pair for energy conservation and growth. Sustained PCE dechlorination by this culture was supported by supplementation with 0.05 mg of vitamin B12 per liter, 25% (vol/vol) anaerobic digestor sludge supernatant, and 2 mM acetate, which presumably served as a carbon source. Neither methanol nor acetate could serve as an electron donor for dechlorination by the H2-PCE culture, and it did not produce CH4 or acetate from H2-CO2 or methanol, indicating the absence of methanogenic and acetogenic bacteria. Microscopic observatios of the pruified H2-PCE culture showed only two major morphotypes: irregular cocci and small rods.